Stress responses due to application of audio or visual stimuli - Bloomer, Caitlin; Hitt, Crystal; Olson, Douglas; Wruck, Colin (Journal of Advanced Student Sciences (JASS), 2014)
Stressful events promote activation of the sympathetic nervous system which causes measurable physiological changes in the body. Visual and auditory inputs often aid in this “fight or flight” stress response if potential harm is detected. In this study, seemingly stressful visual or auditory stimuli were presented to participants. The physiological stress response was assessed by measuring heart rate, skin conductance, and breathing rate before and after exposure to the stimuli. The data was analyzed in order to determine whether audio or visual stimuli elicit a stronger stress response. Our results showed that audio and visual stimuli elicit similar stress responses.
An article that appeared in JASS, issue 2014
Keywords: audio; visual; stress response; respiratory rate; heart rate; skin conductance